Vishnu-014 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ Although the top two hands of the deity carries Shankha and Chakra, the bottom right hand here is carrying a beaded garland, which is unusual in the iconography of Vishnu. This particual avatara of Vishnu needs to be identified. The other hand is broken which makes the identification harder.